Killer instinct - Finder, Joseph (St. Martin's Press, 2006)
Lacking the competitive instincts considered necessary to get ahead in his sales job, Jason Steadman meets a recently-hired Iraq War veteran who recruits him for the company softball team and offers him a job in corporate security.